Politeness Strategies Found in Classroom Interaction Post-Graduate Student - Helmi, Silfia (Modality Journal: International Journal of Linguistics and Literature, 2022)
The science of speech and context is known as pragmatics. Politeness strategy is one of many linguistic concerns covered in this study. There are four categories of politeness in the research on polite discourse that Brown and Levinson pioneered. Being polite seeks to lessen uncomfortable or unwelcome reactions. Culture and politeness can be related through research. The Minangkabau people believe that the use of the "Kato nan ampekâ€ style, which makes one's politeness in speech apparent, can reveal one's politeness. The purpose of this study is to discuss the many types of politeness used in the Postgraduate UNP class. The politeness strategy of Brown and Levinson is the underlying hypothesis. By using data from video zoom meetings for English learning related to teacher and student interactions in the classroom, this research is qualitative and descriptive. Based on the discussion, it is found that they practice all kinds of politeness strategies in leading class for post-graduate studentsPragmatic adalah ilmu tentang ujaran dan konteks.Â  Dalam ilmu ini dibahas beberapa isu dalam berbahasa, salah satunya kesantunan tutur. Didalam kajian tutur kesopanan yang diinisiasi oleh Brwon dan Levinson, memberi empat kategori kesantutan tutur. Kesantunan pada dasarnya bertujuan untuk mengurangi respon yang tidak diinginkan atau ketidaknyamanan. Kajian kesopanan dapat berkorelasi dengan budaya. Kesopanan menurut orang Minangkabau dapat dilihat dari aplikasi â€œkato nan ampekâ€ dari langgam ini, nampak bahwa kesopanan seseorang dalam berujar. Penelitian ini bertujuan untukÂ  mendiskusikan bentuk tutur kesopanan yang ada pada interaksi kelas pada kelas Pasca Sarjana UNP. Teori yang digunakan adalah strategi kesantunan oleh Brown dan Levinson.. Penilitian ini adalah qualitativ descriptif dengan mengambil data dari video zoom meeting pembelajran bahasa Inggris terkait interaksi guru dan murid didalam kelas. Hasil dari penelititan ini menunjukkan empat kategori kesantunan tutur dilakukan oleh dosen kepada mahasiswa pasca sarjana pada interaksi dalam kelas.